Application of Response Surface Methodology in Extraction of Bioactive Component from Palm Leaves (Elaeis guineensis) - Nur Afiqah Arham; Nurul Amal Nadhirah Mohamad; Junaidah Jai; Jagannathan Krishnan; Noorsuhana Mohd Yusof (International Journal of Science and Engineering, 2013)
The hydroxyl groups of the polyphenols are capable to act as reducing agent for reduction reaction. The effect of drying temperature, extraction temperature and extraction duration were evaluated using central composite design which consists of 20 experimental runs. Response surface methodology (RSM) was used to estimate the optimum parameters in extracting polyphenols from the palm leaves. The correspondence analysis of the results yielded a quadratic model which can be used to find optimum conditions of extraction process. The optimum extraction condition of drying temperature, extraction temperature and extraction duration are 70°C, at 70°C of 10 minutes, respectively. Total polyphenols were determined by application of the Folin-Ciocalteu micro method and the extract was found contain of 8 mg GAE/g dry palm leaves at optimum conditions. Doi: 10.12777/ijse.5.2.95-100 [How to cite this article: Arham, N.A., Mohamad, N.A.N., Jai, J., Krishnan, J., Noorsuhana Mohd Yusof, N.M. (2013). Application of Response Surface Methodology in Extraction of Bioactive Component from Palm Leaves (Elaeis guineensis). International Journal of Science and Engineering, 5(2),95-100. Doi: 10.12777/ijse.5.2.95-100